Proses Kelahiran Kerajaan Islam Madinah - W. Ahmad, W. Yahya (Jurnal Usuluddin, 1996)
Muslim scholars have to know more about the development of Islamic State during the time of the Prophet, particularly the Sahifah of Madinah. This article discribes the details of the Prophet's life and his activities when he was the leader of the government of the City State, especially the organization of the Islamic Ummah which was based on definite ideology and a distinct political philosophy, and how the Prophet unified all Muslims and made them one nation confessing one faith, working together as members of a community on which brotherhood was given priority over any other relationship.